Novel side by side Foley catheter balloons for 'extended labour induction': Concept, simulation study and clinical application. (November 2021) - Hofmeyr, G. Justus; Dalmacio, Riche
Highlights: The Foley catheter balloon has safety advantages for labour induction. Uterotonics are used when the balloon is expelled prior to labour. To avoid uterotonics, balloon induction may be extended with side-by-side balloons. Abstract: Objective: To introduce the concept of extended or prolonged mechanical balloon labour induction as opposed to pharmacological methods and amniotomy after single balloon expulsion, by the novel use of side-by-side Foley catheter balloons. This method is of particular relevance when there is prior uterine surgery, fetal reserve is uncertain, the risk of vertical infection is high, or facilities for labour monitoring are limited. Study design: We conducted simulation studies to compare balloon circumferences and resistance to passage through a simulation cervix between different gauge, fluid distension volume and number of Foley catheters. We describe an illustrative clinical case. Results: In simulation studies we found modest increases in Foley catheter balloon circumference with increased catheter gauge and with increasing volume of distending fluid. We found that retention of Foley balloon(s) by a flexible simulated cervix was increased with the gauge, distending volume and number of balloons used side-by-side. We describe the case of a mother with pre-eclampsia with severe features and compromised fetal reserve in whom the side-by-side balloon method achieved spontaneous delivery after a single balloon had been expelled without labour commencing. Conclusions: Institutional protocols for Balloon labour inductions should take into account the characteristics of locally-available balloon catheters. Further research is justified to determine the usefulness of extended mechanical labour induction with side-by-side balloon catheters, particularly with prior caesarean section, uncertain fetal reserve and settings with limited fetal monitoring capacity.